PERBANDINGAN KINERJA KEUANGAN BERDASARJAN RASIO LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS PADA PT INDO TAMBANGRAYA MEGAH TBK DAN PT BUMI RESOURCE MINERALS TBK PERIODE 2019 - 2024 - Nuraulia, Nuraulia; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze and compare the financial performance of PT Indo Tambang Raya Megah Tbk and PT Bumi Resources Minerals Tbk based on liquidity, solvency, and profitability ratios during the period 2019–2024. The research method used is a descriptive comparative method with a quantitative approach. The data used are secondary data in the form of annual financial reports obtained from the official company websites and the Indonesia Stock Exchange. The results show that PT Indo Tambang Raya Megah Tbk has superior financial performance compared to PT Bumi Resources Minerals Tbk. In terms of liquidity, PT Indo Tambang Raya Megah Tbk demonstrates a strong ability to meet its short-term obligations, while PT Bumi Resources Minerals Tbk shows fluctuating performance. In terms of solvency, both companies have relatively low debt levels; however, PT Indo Tambang Raya Megah Tbk exhibits a more stable capital structure. In terms of profitability, PT Indo Tambang Raya Megah Tbk shows a significantly higher ability to generate profits compared to PT Bumi Resources Minerals Tbk. The study concludes that the differences in financial performance between the two companies are influenced by their level of corporate maturity, where PT Indo Tambang Raya Megah Tbk is in a more stable phase, while PT Bumi Resources Minerals Tbk is still in a developmental stage.